Vince and Patricia Whiting embracing in a kiss
Vince and Patricia Whiting sharing a kiss during their eighth and final wedding ceremony at Meridian Park Hospital. A "Mr. & Mrs." balloon is pictured above the "Faith Hope Love" wall decoration in the background.